Pulmonary vascular resistance/systemic vascular resistance (PVR/SVR) ratio changes after sildenafil therapy in uncorrected congenital heart disease-associated pulmonary arterial hypertension - Evita Devi Noor Rahmawati; Putrika Prastuti Ratna Gharini; Anggoro Budi Hartopo; Lucia Kris Dinarti; Dyah Wulan Anggrahini (Universitas Gadjah Mada, 2023)
Pulmonary vascular resistance (PVR) to systemic vascular resistance (SVR) ratio is a prognostic predictor in congenital heart disease (CHD)-associated pulmonary arterial hypertension (PAH) after defect correction. Sildenafil, widely used as a PAH drug, can decrease PVR with minimal or without changes in SVR, resulting in decreased PVR/SVR ratio after treatment. However, there is limited evidence that PVR/SVR ratio reduced after sildenafil therapy in uncorrected CHD-associated PAH patients. This study aimed to investigate the decreasing of the PVR/SVR ratio after ≥ 1-year oral sildenafil therapy in adult uncorrected CHD-associated PAH. A total of 30 uncorrectable CHD-associated PAH subjects derived from the COHARD-PH registry were included in this study. Right heart catheterization (RHC) was performed during the first visit and further evaluations were conducted after ≥1-year oral sildenafil therapy. The PVR/SVR ratio at the baseline and after the evaluation was collected. The primary outcome of this study was the changes in PVR/SVR ratio from baseline to evaluated RHC. Characteristic analysis of subjects with decreased PVR or PVR/SVR ratio was perforemd as the secondary outcome. The mean PVR and SVR were not different from baseline and evaluated RHC (15.98± 10.67 vs. 18.38±13.93 WU, p=0.206 and 36.65±13.99 vs. 39.34±15.46 WU, p=0.262). There was no significant difference in the baseline PVR/SVR ratio and the evaluated PVR/SVR ratio after ≥1-year sildenafil therapy (0.48 ±0.32 vs. 0.49±0.36; p=0.882). As much as 15 subjects (50%) experienced decreased PVR/SVR ratio. However, there was no significant difference in the characteristics, including age, Eisenmenger syndrome, type of shunts, baseline PVR, PAH-specific treatment, and baseline NT-proBNP level (p>0.05). In conclusion, sildenafil therapy does not change PVR/SVR ratio in adults with uncorrected CHD-associated PAH.